Nirvāṇa and the ten Dharmas in the Altun Yaruk Sudur text - Kübra; Hacer (Uluslararası Türk Lehçe Araştırmaları Dergisi)
Buddhism is a path based on understanding the fundamental truths of life and attaining enlightenment. Nirvāṇa is the ultimate goal of this path. On this journey, the concept of nirvāṇa and the ten dharmas associated with it hold significant importance. According to Buddhist thought, the ten dharmas serve as a guide that enables a being to progress on the right path. In the concept of nirvāṇa explained by the Tathāgatas (Buddhas), emphasis is placed on these ten fundamental characteristics. These ten features explain the state of enlightenment of the Buddhas and how they perceive the truth. They demonstrate how a being can attain absolute reality, that is, nirvāṇa. They express how the Buddhas comprehend the nature of truth and ultimate peace through enlightenment. Through these ten dharmas, Buddhas establish complete harmony between individual and universal reality. Additionally, as enlightened beings, they aim to guide all other beings through these ten dharmas. Nirvāṇa does not merely represent a state but signifies the transformation of all existence and the complete realization of truth. It is the key to liberation from the cycle of birth and death. It shows that it is possible for a being to be freed from suffering. Furthermore, when a being attains nirvāṇa, they reach the peak by achieving complete freedom. By embracing nirvāṇa and the ten dharmas associated with it, a being not only transforms themselves but, according to the Mahāyāna school, also positively influences the other beings around them. This contributes to leading a conscious, harmonious, and meaningful life. As a result, the sense of responsibility of the being towards both themselves and their surroundings increases. A being who fulfills these responsibilities attains nirvāṇa, the state of peace. In this study, the concept of nirvāṇa in the Altun Yaruk Sudur text and all the terms that express the concept of nirvāṇa will be identified, and the semantic characteristics of these terms will be analyzed in detail.